A preliminary study on speech recognition in noise training for children with hearing loss. (October 2021) - Zhang, Mengchao; Moncrieff, Deborah; Johnston, Deborrah; Parfitt, Michelle; Auld, Ruth
Abstract: Purpose: The current study is a preliminary study to examine whether children with hearing loss would benefit from a speech recognition in noise training. Methods: Twenty-five children who wore hearing aids, cochlear implants, or bimodal devices from 4 to 12 years old participated in the study (experimental, n = 16; control, n = 9). The experimental group received a speech-in-noise training that took sixteen 15-min sessions spanning 8 to 12 weeks. The task involves recognizing monosyllabic target words and sentence keywords with various contextual cues in a multi-talker babble. The target stimuli were spoken by two females and fixed at 65 dB SPL throughout the training while the masker varied adaptively. Pre- and post-training tests measured the speech recognition thresholds of monosyllabic words and sentences spoken by two males in the babble noise. The test targets were presented at 55, 65, and 80 dB SPL. Results: The experimental group improved for word and sentence recognition in noise after training (Mean Difference = 2.4–2.5 dB, 2.7–4.2 dB, respectively). Training benefits were observed at trained (65 dB SPL) and untrained levels (55 and 80 dB SPL). The amount of post-training improvement was comparable between children using hearing aids and cochlear implants. Conclusions: This preliminary study showed that children with hearing loss could benefit from a speech recognition in noise training that may fit into the children's school schedules. Training at a conversational level (65 dB SPL) transfers the benefit to levels 10–15 dB softer or louder. Training with female target talkers transfers the benefit to male target talkers. Overall, speech in noise training brings practical benefits for school-age children with hearing loss.